Review of the Capsalinae (Monogenea: Capsalidae) - Chisholm, Leslie A.; Whittington, Ian D. (Zootaxa, 2007)
The Capsalinae Baird, 1853 (Monogenea: Capsalidae) is revised based on a thorough review of original descriptions and examination of type museum material, where available, to validate species. A total of 262 type and voucher specimens was studied representing apparently 42 of the 60 currently described capsaline species. A combination of characters that should be independent of variation due to specimen preparation techniques was chosen to discriminate species. These characters include the presence/absence of papillae on the ventral surface of the haptor, the presence/absence and the morphology of haptoral accessory sclerites and the presence/absence of dorsomarginal body sclerites and their morphology and distribution. We consider that only 36 of the 60 nominal capsaline species are valid. We could find no support for Caballerocotyla Price, 1960 and therefore we synonymise it with Capsala Bosc, 1811. Under the current concept we recognise 22 species of Capsala, 7 species of Capsaloides Price, 1938, 3 species of Nasicola Yamaguti, 1968 and 4 species of Tristoma Cuvier, 1817. The following Capsala species are considered valid: C. albsmithi (Dollfus, 1962) n. comb.; C. biparasitica (Goto, 1894) Price, 1938; C. caballeroi Winter, 1955; C. foliacea (Goto, 1894) Price, 1938; C. gouri Chauhan, 1951; C. gregalis (Wagner & Carter, 1967) n. comb.; C. interrupta (Monticelli, 1891) Johnston, 1929; C. katsuwoni (Ishii, 1936) Price, 1938; C. laevis (Verrill, 1875) Johnston, 1929; C. maccallumi Price, 1939; C. magronum (Ishii, 1936) Price, 1938; C. manteri Price, 1951; C. manteriaffinis (Mamaev, 1968) n. comb.; C. martinierei Bosc, 1811; C. notosinense (Mamaev, 1968) n. comb.; C. nozawae (Goto, 1894) Price, 1938; C. onchidiocotyle (Setti, 1899) Johnston, 1929; C. ovalis (Goto, 1894) Price, 1938; C. paucispinosa (Mamaev, 1968) n. comb.; C. pelamydis (Taschenberg, 1878) Price, 1938; C. poeyi (Pérez-Vigueras, 1935) Price, 1938; C. pricei Hildago-Escalente, 1950. We consider the following Capsaloides species valid: C. cornutus (Verrill, 1875) Price, 1938; C. cristatus Yamaguti, 1968; C. hoffmannae Lamothe-Argumedo, 1996; C. magnaspinosus Price, 1939; C. nairagi Yamaguti, 1968; C. perugiai (Setti, 1898) Price, 1938; C. sinuatus (Goto, 1894) Price, 1938. The following Nasicola species are deemed valid: N. brasiliensis Kohn, Baptista-Farias, Santos & Gibson, 2004; N. hogansi Wheeler & Beverley-Burton, 1987; N. klawei Stunkard, 1962. Presently, we consider the following Tristoma species valid: T. adcoccineum Yamaguti, 1968; T. adintegrum Yamaguti, 1968; T. coccineum Cuvier, 1817; T. integrum Diesing, 1850. A list of new and re-established synonyms is provided. The status of each species is discussed in detail and a key to all capsaline species that we consider valid is presented. The following 5 capsaline species are considered to be species inquirendae: Caballerocotyla phillippina Velasquez, 1982; Capsala megacotyle (Linstow, 1906) Johnston, 1929; Tristoma fuhrmanni Guiart, 1938; T. levinsenii Monticelli, 1891; T. uncinatum Monticelli, 1889. The importance of careful character selection to discriminate between capsaline species and the need for studies of live parasites to obtain additional characters based on reproductive structures is addressed. Hostspecificity in the Capsalinae is also discussed.